A long sleep duration can be harmful for health - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Two studies from recently published were designed to investigate the effect of sleep duration on health. And both of them carry out bad news for those who like to sleep long.